Entre trilhos e trilhas: vivências, cotidiano e intervenções na cidade Uberlândia/ MG 1970-2006 - Ramos, Geovanna de Lourdes Alves (2007)
This dissertation investigates the trajectories, marks, memories and experiences of the inhabitants of the city of Uberlândia/MG, making analysis in the ways to live in the city, with the dispute of spaces and territories. One is about a quarrel on the withdrawal of the Railroad station of the Mogiana Company of the central area in the decade of 1970 and of the construction of the Avenue João Naves de Avila in the old stream bed of this railroad, beyond other occured changes in this social space. I analyze here the process of reorder of the urban space after the demolition of the station, specifically, of the railway tracks, from the experiences told and lived for inhabitants of the city. I search to point some thematic clipping possibilities new and the emergency of other citizens in the reading of these interventions and, in this way, to dialogue with the carried through readings until then. The consulted and worked sources are the local periodicals, tax Acts of the City council, photographs, tables and the narratives of inhabitants, where I analyze the daily one of Uberlândia, its permeate contradictions of changes and stabilities. This documentary made possible me the inquiry of different dimensions in the ways of living of the social citizens in the city, as well as its social relations added the tensions for generated them, analyzing the process of social transformation and the way as they coexisted and circulated in the territories, producing and dealing with the urban interventions.